The populist politics of Euroscepticism in times of crisis: Comparative conclusions. (August 2018) - Pirro, Andrea LP; Taggart, Paul; van Kessel, Stijn
This article offers comparative findings of the nature of populist Euroscepticism in political parties in contemporary Europe in the face of the Great Recession, migrant crisis, and Brexit. Drawing on case studies included in the Special Issue on France, Germany, Greece, Italy, the Netherlands, Portugal, Spain, and the United Kingdom, the article presents summary cross-national data on the positions of parties, the relative importance of the crisis, the framing of Euroscepticism, and the impact of Euroscepticism in different country cases. We use this data to conclude that there are important differences between left- and right-wing variants of populist Euroscepticism, and that although there is diversity across the cases, there is an overall picture of resilience against populist Euroscepticism.